Eppur si muove : Art and Technology, A Shared Sphere : A Collaboration between the Mudam Luxembourg and the Musée des Arts et Métiers - CNAM, Paris. - Staes, Pascale; Theisen, Carole (Luxembourg : Mudam éditions, 2015)
Allouche, Dove ; Almond, Darren ; Auguste-Dormeuil, Renaud ; Berthier, Julien ; Beutler, Michael ; Bochner, Mel ; Bock, Katinka ; Brouwn, Stanley ; Burden, Chris ; Canell, Nina ; Cramer, Daniel Gustav ; Csörgö, Attila ; Dahlem, Björn ; Dekyndt, Edith ; Delvoye, Wim ; Elíasson, Ólafur ; Fink, Christoph ; Gego ; Gerner, Jochen ; Godinho, Marco ; Granjon, Paul ; Grönlund-Nisunen ; Gusmão, João Maria + Paiva, Pedro ; Guyton, Wade ; Horn, Rebecca ; Van Hove, Éric ; Janssens, Ann Veronica ; Joumard, Véronique ; Jugnet, Anne Marie + Clairet, Alain ; Julius, Rolf ; Kawara, On ; Kirps, Paul ; Kowalski, Piotr ; Krier, Sophie ; Kwade, Alicja ; Lamarche, Bertrand ; Lamelas, David ; Lamouroux, Vincent ; Lewis, Katie ; Macchi, Jorge ; Martin, Daria ; Martin, Kris ; Miyajima, Tatsuo ; Miyamoto, Kazuko ; Montaron, Laurent ; Motti, Gianni ; Nicolai, Carsten ; Nuur, Navid ; Oppenheim, Lisa ; Ortega, Damián ; Paci, Adrian ; Paglen, Trevor ; Paik, Nam June ; Palma, Miguel ; Panamarenko ; Paysant, Michel ; Pica, Amalia ; Prévieux, Julien ; Richer, Evariste ; Rousse, Georges ; Ruff, Thomas ; Sautour, Stéphane ; Schmidt Hansen, Lasse ; Shawcross, Conrad ; Starling, Simon ; Stelarc ; Struth, Thomas ; Takis ; Tinguely, Jean ; Tropa, Francisco ; van der Werve, Guido ; Widener, George ; Wood, John + Harrison, Paul ; Zarka, Raphaël
Eppur si muove. Art and Technology, A Shared Sphere, Mudam Luxembourg, Luxembourg, 09.07.2015-17.01.2016
boek